19. Visual cortex representation of the vertical meridian. Issue 12 (December 2016) - Rinalduzzi, S.; Jones, S.J.; Vingolo, E.M.; Fattapposta, F.; Currà, A.
Abstract : Two neural mechanisms warrant transmission of visual information to both hemispheres: the corpus callosum, most represented at secondary visual cortices (V2–V3–V4–V5); the 0.5 deg wide band of nasal retina near the fovea, which contains ganglion cells projecting to ipsilateral LGN/striate cortex intermingled with cells that project contralaterally. We investigated visual projections at the vertical meridian of the visual field to the visual cortex, by studying visual evoked potentials (VEPs) in ten healthy subjects. With binocular viewing of the pattern reversal checkerboard, we used either left/right hemifield stimulation either upper/lower hemifield stimulation. Alternating right and left hemifield stimulation with extension of edges across the vertical meridian (binding recordings) and complementary reversal (unbinding recordings) was used for test recordings. Alternating upper and lower hemifield stimulation were used as control recordings. N75 did not differ in binding/unbinding and control recordings. P100 and N145 amplitude were higher - and P100 latency shorter – during binding than unbinding recordings. Control recordings showed no difference between upper/ lower hemifield stimulation. These findings suggest that visual stimuli with extension of edges across the vertical meridian are mainly represented at the level of visual peristriate areas.